Verbal and Nonverbal Types of Communication Strategies - Qochqorova Zulfizar Abduxamid qizi; Mirzaxubaydinov Nurjahon Hikmatullao’g’li (Journal of Innovation in Education and Social Research, 2023)
Communication is an important part of human interaction and can be divided into verbal and non-verbal types. This article aims to explore different communication strategies and their impact on interpersonal relationships.